Penentuan Kadar Rubraxanton pada Ekstrak Kulit Batang Garcinia spp - Susanti, Meri; Dachriyanus, .; Putra, Deddy Prima; Sriwahyuni, Fatma (Jurnal Farmasi Indonesia, 2013)
In this study a High Performance Liquid Chromatography (HPLC) has been used for determination of rubraxanton on bark extracts Garcinia spp (Garcinia mangostana, Garcinia Cowa, Garcinia griffitii, Garcinia dioica and Garcinia forbesii). HPLC system consisted of C-18 reversed phase column with a length of 250 mm, diameter 4.6 mm, 20 mL injection volume, mobile phase methanol: water (gradient system with polarity) and flow rate of 1ml/min. Rubraxanton levels obtained in this study; 9.161% for G.mangostana, 6.942% for G.cowa, 6.762% for G.dioica, 0.499% for G.forbesii and 0.229% for G.griffitii. The method has been validated for specificity, linearity, accuracy, precision, limits of detection (LOD) and limits of quantitation (LOQ). The linearity of the method can be seen from the regression coefficient r=0.9996 with a linearity range from 1.72 to 55 ug/ml. Recovery of rubraxanton in the extract of G.mangostana was between 99.61 to 101.08%. Intra and inter day precision showed relatively small level of standard deviation (lower than 2%). Limit Of Detection (LOD) and Limit Of Quantitation (LOQ) are 0.55 ug/ml and 1.82 ug/ml respectively.Keywords : rubraxanton, bark extracts, Garcinia spp.